2012
DOI: 10.1167/12.3.4
|View full text |Cite
|
Sign up to set email alerts
|

The role of discrepant retinal motion during walking in the realignment of egocentric space

Abstract: Visually guided action relies on accurate perception of egocentric direction. Unfortunately, perceived direction easily becomes misaligned. How is this problem overcome? One theory (R. Held & S. J. Freedman, 1963) is that during self-movement the observer uses the relationship between anticipated and experienced sensory feedback as a source of information to maintain alignment. However, data supporting this theory is equivocal, and recent evidence appears contradictory. We reexamined the issue. We injected an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…The reduction from the first to fourth trial was, in order of magnitude, 3.02° (SD = 3.19°) in the Cloud environment, 1.99° (SD = 4.23°) in the Room, 1.33° (SD = 3.26°) in the Outline and 1.28° (SD = 3.29°) in the Line environment. This ordering ( Line < Outline < Room < Cloud ) does reflect the richness of optic flow across environments and is compatible with earlier work (Herlihey & Rushton, 2012).…”
Section: Longer Term Impact Of Optic Flow On Visually Guided Walkingsupporting
confidence: 89%
See 2 more Smart Citations
“…The reduction from the first to fourth trial was, in order of magnitude, 3.02° (SD = 3.19°) in the Cloud environment, 1.99° (SD = 4.23°) in the Room, 1.33° (SD = 3.26°) in the Outline and 1.28° (SD = 3.29°) in the Line environment. This ordering ( Line < Outline < Room < Cloud ) does reflect the richness of optic flow across environments and is compatible with earlier work (Herlihey & Rushton, 2012).…”
Section: Longer Term Impact Of Optic Flow On Visually Guided Walkingsupporting
confidence: 89%
“…Before concluding, it is important to look further. Richness of optic flow may prove a good predictor of trajectory over a longer time frame: Exposure to discrepant visual feedback (as happens in our experiment) leads to a process of adaptation, either of perception ( Rushton & Salvucci, 2001;Herlihey & Rushton, 2012), and/or of perceptual-motor mappings (Bruggeman et al, 2007). Such an adaptation would change the trajectories taken.…”
Section: Longer Term Impact Of Optic Flow On Visually Guided Walkingmentioning
confidence: 60%
See 1 more Smart Citation
“…Accordingly, the effect of optic flow observed in previous walking studies could be due to the shifted perceived target egocentric direction rather than the use of heading. Indeed, it has been shown that after walking for a period of time with prism glasses that displaced heading specified by optic flow away from the straight-ahead, observers perceived their straight-ahead to be biased toward the displaced heading (Held and Bossom 1961;Herlihey and Rushton 2012;Morton and Bastian 2004;Redding and Wallace 1985). With the use of a visual control of steering task, Li et al (2012) also found that the longer one steers toward a target with displaced heading, the larger the shift of the perceived straight-ahead.…”
Section: Current Studymentioning
confidence: 99%
“…There has been a finding of a larger OLP after-effect compared to SAP after-effect following a full decay of the VSA after-effect (Hatada, Rossetti, & Miall, 2006), and observations of greater OLP after-effects compared to combined VSA and SAP after-effects (e.g., Welch, Choe, & Heinrich, 1974). Reports from studies finding no visual after-effect in healthy people have also accumulated (Bornschlegl et al, 2012;Harris, 1963;Herlihey & Rushton, 2012;Michel, Gaveau, Pozzo, & Papaxanthis, 2013;Morton & Bastian, 2004;Newport, Preston, Pearce, & Holton, 2009). The lack of observable visual after-effect in many studies alongside the pattern of deviations from linear additivity suggest that there might be an issue with how the VSA after-effect has previously been measured, or how the visuomotor change is understood.…”
Section: Accepted Manuscriptmentioning
confidence: 99%